Effects of small interfering RNA-mediated silencing of susceptibility genes of non-syndromic cleft lip with or without cleft palate on cell proliferation and migration. (November 2020) - Li, Meng-Xue; Li, Zheng; Zhang, Rui; Yu, Yue; Wang, Lu-Shan; Wang, Qi; Ding, Zhen; Zhang, Jin-Peng; Zhang, Mei-Rong; Xu, Li-Chun
Abstract: Background: Non-syndrome cleft lip with or without cleft palate (NSCL/P) is the most common congenital defect with a complex etiology involving both genetic and environmental factors. Our previous research has identified susceptibility genes of NSCL/P using whole-exome sequencing. The study was to determine the effects of small interfering RNA (siRNA)-mediated silencing of genes on cell proliferation and migration to confirm the roles of the genes in NSCL/P. Methods: We silenced the genes by RNA interference (RNAi) with siRNA in human oral keratinocyte (HOK). We used the Cell Counting Kit-8 (CCK8) assay to determine cell proliferation and the wound healing assay to determine cell migration. Results: Migration of HOK was inhibited by RNAi-induced silencing of adenosine triphosphate binding cassette transporter A4 ( ABCA4 ), erythropoietin produces hepatocyte A receptor 3 ( EPHA3 ), alpha-parvin ( PARVA ), and platelet-derived growth factor C ( PDGFC ). The change of proliferation was not found. Treated with siRNA-mediated silencing of type IV collagen ( COL4A2 ), eukaryotic translation initiation factor 2B subunit ( EIF2B3 ), fibroblast growth factor receptor 2 ( FGFR2 ), kinesin family member 20B ( KIF20B ), β-lactamase serine-like protein ( LACTB ), SEC16 homolog A ( SEC16A ) and thyroid adenoma target gene ( THADA ) had no effects on cell proliferation and migration of HOK. Conclusions: We suggest mutations of the four susceptibility genes ABCA4, EPHA3, PARVA and PDGFC are involved in NSCL/P through inhibiting cell migration. The study provides new candidates for future study of NSCL/P.